Conflicting demands of No Child Left Behind and state systems: Mixed messages about school performance. - Linn, Robert L. (Education Policy Analysis Archives, 2005)
An ever-increasing reliance on student performance on tests holds schools and educators accountable both to state accountability systems and also to the accountability requirements of the No Child Left Behind (NCLB) Act of 2001. While each state has constructed its own definition of Adequate Yearly Progress (AYP) requirements within the confines of NCLB, substantial differences between the accountability requirements of many state systems and NCLB still have resulted in mixed messages regarding the performance of schools. Several features of NCLB accountability and state accountability systems contribute to the identification of a school as meeting goals according to NCLB but failing to do so according to the state accountability system, or vise versa. These include the multiple hurdles of NCLB, the comparison of performance against a fixed target rather than changes in achievement, and the definition of performance goals. The result of these features is a set of AYP measures that is inconsistent both with existing state accountability systems and also with state NAEP performance. Using existing achievement to set the cut-score measured by AYP and using the highest-performing schools to set the year-to-year improvement standards would improve the NCLB accountability system.